2018
DOI: 10.1016/j.otsr.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

No lower bacterial adhesion for ceramics compared to other biomaterials: An in vitro analysis

Abstract: IV, in vitro study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It has been recently shown that bacterial adhesion is less important on porous alumina than on other materials such as titanium or stainless steel, 16,17 which is another asset in surgeries with risks of infection such as wide oncologic excision of the sternum.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that bacterial adhesion is less important on porous alumina than on other materials such as titanium or stainless steel, 16,17 which is another asset in surgeries with risks of infection such as wide oncologic excision of the sternum.…”
Section: Discussionmentioning
confidence: 99%
“…The results can be compared to each other, since bacterial adhesion seems to be similar on different materials (i.e. cobalt-chrome, ceramics, titanium, polyethylene) 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a new approach was suggested in which the implants are coated with a defensive antibacterial-coating hydrogel, which is supposed to reduce bacterial adhesion and biofilm formation [ 130 ]. Although the data on direct bacterial adhesion and biofilm formation on ceramic articulating surfaces in contrast to CoCr and Polyethylene remain controversial [ 137 , 138 ], the use of ceramic heads has been reported to be associated with a lower risk of revision for periprosthetic joint infection [ 139 ]. Hosman et al [ 140 ] suggested that wear debris from metal-on-metal bearing surfaces might accelerate the growth of bacteria.…”
Section: Current Trends and Future Perspectivesmentioning
confidence: 99%